Firm organization with multiple establishments - Anna Gumpert; Henrike Steimer; Manfred Antoni (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
How do geographic frictions affect firm organization? We show theoretically and empirically that geographic frictions increase the use of middle managers in multi-establishment firms. In our model, we assume that a CEO's time is a resource in limited supply, shared across headquarters and establishments. Geographic frictions increase the costs of accessing the CEO. Hiring middle managers at one establishment substitutes for CEO time, which is reallocated across all establishments. Consequently, geographic frictions between the headquarters and one establishment affect the organization of all establishments of a firm. Our model is consistent with novel facts about multi-establishment firm organization that we document using administrative data from Germany. We exploit the opening of high-speed train routes to show that not only the establishments directly affected by faster travel times but also the other establishments of the firm adjust their organization. Our findings imply that local conditions propagate across space through firm organization.
Keywords: D21; D22; D24; 330; firm organization; multi-establishment firm; knowledge hierarchy; geography